Governance Arrangements for State Owned Enterprises - Vagliasindi, Maria (World Bank, Washington, DC, 2012)
The aim of this paper is to shed new light on key challenges in governance arrangements for state owned enterprises in infrastructure sectors. The paper provides guidelines on how to classify the fuzzy and sometimes conflicting development goals of infrastructure and the governance arrangements needed to reach such goals. Three policy recommendations emerge. First, some of the structures implied by internationally adopted principles of corporate governance for state owned enterprises favoring a centralized ownership function versus a decentralized or dual structure have not yet been sufficiently "tested" in practice and may not suit all developing countries. Second, general corporate governance guidelines (and policy recommendations) need to be carefully adapted to infrastructure sectors, particularly in the natural monopoly segments. Because the market structure and regulatory arrangements in which state owned enterprises operate matters, governments may want to distinguish the state owned enterprises operating in potentially competitive sectors from the ones under a natural monopoly structure. Competition provides not only formidable benefits, but also unique opportunities for benchmarking, increasing transparency and accountability. Third, governments may want to avoid partial fixes, by tackling both the internal and external governance factors. Focusing only on one of the governance dimensions is unlikely to improve SOE performance in a sustainable way.